Pocket business dictionary : Polish-English, English-Polish - Woytowicz-Neymann, Monika; Malec, Jerzy (Warszawa : POLTEX, 1992)
A two volume pocket dictionary of business terms for use by business travelers to Poland.
Polish and English.
Keywords: Business -- Dictionaries -- Polish; Polish language -- Dictionaries -- English; English language -- Dictionaries -- Polish